A Short Overview of Curcuma aeruginosa with Curative Potentials Against COVID-19 - Paramita, Swandari; Ismail, Sjarif; Bachtiar Moerad, Emil; Marliana, Eva (Asian Journal of Chemistry, 2021)
COVID-19 (coronavirus disease) is an infectious disease of the respiratory tract caused by SARS-CoV-2. Nature has provided a great source of antiviral compounds, from which innovative products for the treatment of COVID-19 can be produced. One of the medicinal plants that can be developed for the treatment of COVID-19 is Curcuma aeruginosa Roxb. Previous studies have found tracheospasmolytic and anti-inflammatory activity of this indigenous Curcuma species. There are 10 chemical compounds from Curcuma aeruginosa that have been proven against COVID-19, namely 1,8-cineole (eucalyptol), α-terpineol, β-caryophyllene, β-eudesmol, β-pinene, β-sitosterol, curcumenol, palmitic acid, succinic acid and zingiberene. Further research is needed for C. aeruginosa to become a new antiviral drug for the treatment of COVID-19.